Reaction kinetics of typical inorganic salts in H2–Air explosion suppression and the synergistic regulation mechanism of multi-elements - Qiuhong Wang; Rui Guo; Zhenmin Luo; Hu Wen; Xianfeng Chen; Wenzhe Mao; Qingfeng Wang; Qiulin Li; Yifan Li (Chemical Engineering Journal, 2026)

Lymph node-targeted H2S-self-releasing multifunctional prodrug for the dual remodeling of immunological and redox homeostasis in autoimmune uveitis - Qinjin Dai; Yuelan Wu; Wenbo Geng; Mengna Li; Wanyun Zhang; Yuxian Lai; Pei Zhang; Xiaoyue Zhang; Chunjiang Zhou; Yinuo Wang; Qingfeng Cao; Xiang Luo; et al. (Chemical Engineering Journal, 2026)

An onboard ultra-rapid orbit determination strategy for LEO satellite utilizing spaceborne GNSS data - Peng Luo; Yezhi Song; Xiaogong Hu; Qingfeng Wu; Jianhua Yang; Kai Li; Chengpan Tang; Changshao Chen (Advances in Space Research, 2026)

A star’s death by a thousand cuts: the runaway periodic eruptions of AT2023uqm - Yibo Wang; Tinggui Wang; Shifeng Huang; Jiazheng Zhu; Ning Jiang; Wenbin Lu; Rongfeng Shen; Shiyan Zhong; Dong Lai; Yi Yang; Xinwen Shu; Tianyu Xia; et al. (Science Bulletin, 2026)

Targeting the Wnt/β-catenin pathway: veratramine mitigates MNNG-induced gastric precancerous lesions - Pan Zhang; Xuelin Sun; Longteng Liu; Yatong Zhang; Jiaqi Bo; Wenli Huang; Yifan Na; Jingyi Zhang; Xiaoyun Qin; Qingfeng Luo (Molecular and Cellular Biochemistry, 2026)

AI-designed crop populations for sustainable intensification - Ning Luo; Junhan Wang; Morten Graversgaard; Renan C. Umburanas; De Li Liu; Qirui Li; Jonathan Storkey; Simon Willcock; Pu Wang; Qingfeng Meng (Trends in Plant Science, 2026)

Synergistic effects of the dual pilot policy on pollution reduction and carbon mitigation: The role of data empowerment and market mechanisms - Qingfeng Luo; Fenfen Wang; Can Wang; Xinyang Dong (Journal of Cleaner Production, 2026)

Underlying mechanism and the effect of diacylglycerols on the protein structural stability and in vitro digestibility of pork meatballs - Xinxin Zhao; Yunling Jiang; Zixin Luo; Xiankun Sun; Jiangyu Zhu; Hai Yu; Xinyan Peng; Qingfeng Ge (Food Chemistry, 2026)

Effect of Mg(OH)2 addition on NH4H2PO4 powder in suppressing the explosion of volatile mixtures of methane and coal - Qiuhong Wang; Rui Guo; Jun Deng; Zhenmin Luo; Chi-Min Shu; Zezhou Song; Qingfeng Wang; Junjie Wu; Di Wu; Ran Liu (Chemical Engineering Journal, 2026)

Macro‐Hybrid and Micro‐Hybrid of Fish - Qizhi Liu; Anmin Liao; Min Tao; Qinbo Qin; Kaikun Luo; Chun Zhang; Shi Wang; Yi Zhou; Fangzhou Hu; Yude Wang; Chang Wu; Wuhui Li; et al. (Reviews in Aquaculture, 2026)
This study reviews the progress in fish breeding, focusing on distant hybridization and gynogenesis, and introduces the theory of macro‐hybrid and micro‐hybrid. The macro‐hybrid refers to the allo‐progeny derived from distant hybridization, including the allo‐progenies. The micro‐hybrid refers to the auto‐progenies derived from distant hybridization or heterologous sperm‐induced gynogenesis, which possess a genome derived predominantly from the maternal but contain DNA fragments originating from the paternal. Macro‐hybrids induce significant phenotypic changes, while micro‐hybrids improve growth rate and stress resistance. Both hybridization and gynogenesis exhibit high selective pressure. This review elucidates how selective pressures (homozygosity + heterologous sperm + cold/heat shock) of the heterologous sperm‐induced gynogenesis contribute to the generation of effective genetic variations. The study also presents the technologies of macro‐hybrid and micro‐hybrid. In macro‐hybrids of distant hybridization, parental chromosome numbers are closely matched, enabling the formation of fertile allo‐diploid and allo‐tetraploid strains. In micro‐hybrid of distant hybridization, equal or differing chromosome numbers between parents yield fertile auto‐tetraploid and auto‐diploid strains. In micro‐hybrid of heterologous sperm‐induced gynogenesis, equal or different chromosome numbers between parents yield auto‐diploid strains. The integration of heterologous sperm‐induced gynogenesis, back‐cross, and self‐cross strategies can address the issue of all‐female progeny resulting from gynogenesis. A series of auxiliary breeding techniques is established to support the macro‐hybrid and micro‐hybrid breeding. Case studies of superior fish strains developed through macro‐hybrid and micro‐hybrid breeding are presented. The establishment of macro‐hybrid and micro‐hybrid theory and breeding technologies holds significant value for fish breeding.

Cover Image - Qizhi Liu; Anmin Liao; Min Tao; Qinbo Qin; Kaikun Luo; Chun Zhang; Shi Wang; Yi Zhou; Fangzhou Hu; Yude Wang; Chang Wu; Wuhui Li; et al. (Reviews in Aquaculture, 2026)
The cover image is based on the article Macro‐Hybrid and Micro‐Hybrid of Fish by Shaojun Liu et al., https://doi.org/10.1111/raq.70106 . image

Hydrodynamics knowledge-driven path planning for safety-constrained energy-saving in amphibious unmanned ground vehicles - Jun Luo; Jing Huang; Huayan Pu; Fanglong Wang; Qingfeng Li; Gang Wang; Mingyang Liu (Ocean Engineering, 2025)

Integrated Analysis of Phenotypic and Hepatic Transcriptomic Profiles Reveals Enhanced Cold Tolerance in Triploid Crucian Carp - Suifei Tao; Zexun Zhou; Shandong Chen; Jialin Cui; Yude Wang; Kaikun Luo; Wei Liu; Qingfeng Liu; Wuhui Li; Shaojun Liu (Fishes, 2025)
Cold stress poses a critical threat to fish survival by triggering metabolic dysfunction, oxidative damage, immune suppression, and apoptosis. However, hybrid polyploid fish triploid crucian carp (3nRCR, 3n = 150) demonstrate superior stress tolerance. In this study, we investigated the cold adaptation mechanisms in different ploidy cyprinid fishes: triploid crucian carp compared to its diploid improved red crucian carp (Carassius auratus red var., RCC, 2n = 100, ♀) and improved allotetraploid (4nAT, 4n = 200, ♂) progenitors. Under controlled cooling, 3nRCR lost equilibrium at a significantly lower temperature (3.2 °C) than RCC (4.0 °C) and 4nAT (4.5 °C), confirming its superior enhanced cold resistance. Histological examination revealed minimal tissue damage in 3nRCR, characterized by reduced gill inflammation and cellular apoptosis. Transcriptomics revealed triploid-specific molecular strategies: 3nRCR uniquely activated retinol metabolism and metabolic rewiring (arginine/proline metabolism, oxidative phosphorylation). Notably, in the immune-related NLR signaling pathway, both nlrp1 and nlrp3 (key inflammasome components) were significantly downregulated in 3nRCR (p

Sb3+-doped terbium-based metal halide with efficient dual band emission for ratiometric temperature sensing - Zhe Tang; Xiaochen Wang; Shuyue Wang; Maria Syskaki; Qingfeng Wei; Binbin Fan; Chenxin Fan; Dandan Luo; Tianxin Bai; Junsheng Chen (Chemical Engineering Journal, 2025)

Reduced serum levels of mitochondria-derived peptide MOTS-c in patients with obstructive sleep apnea - Zhuoding Luo; Rui Ji; Renjing Ye; Yawen Shi; Qingfeng Pang; Min Yin (Sleep and Biological Rhythms, 2025)

Characterization of flavor profiles of water-boiled pork meatballs at different ultrasonic powers using solid-phase microextraction gas chromatography–mass spectrometry combined with electronic nose - Xinxin Zhao; Bangcheng Lai; Yunling Jiang; Xiankun Sun; Zixin Luo; Qingfeng Ge; Jiaxin Chen; Hai Yu (Meat Science, 2025)

The impact of artificial intelligence development on embodied carbon emissions: Perspectives from the production and consumption sides - Qingfeng Luo; Jingyuan Wang (Energy Policy, 2025)

The Research Advances in Distant Hybridization and Gynogenesis in Fish - Qizhi Liu; Shi Wang; Chenchen Tang; Min Tao; Chun Zhang; Yi Zhou; Qinbo Qin; Kaikun Luo; Chang Wu; Fangzhou Hu; Yude Wang; Qingfeng Liu; et al. (Reviews in Aquaculture, 2025)
Distant hybridization and gynogenesis are two prevalent breeding techniques for fishes. Drawing from the research achievements of our team and the existing literature, we summarize the reproductive traits and genetic features of fishes derived from distant hybridizations and gynogenesis, and we deduce the fundamental mechanisms of these two methods and compare them, discerning their common and different characteristics. Both distant hybridization and gynogenesis techniques can alter genotypes and phenotypes, thus establishing them as significant breeding methods. Additionally, the genetic principles and the basic biological characteristics of distant hybridization and gynogenesis in fish have been inferred. We propose the concepts of macro‐hybrid and micro‐hybrid based on extensive experimental findings from fish distant hybridizations and gynogenesis. The term “macro‐hybrid” refers to offspring from distant hybridization that possess two distinct subgenomes, each inherited from one of the two parental species, such as allodiploid and allotetraploid lineages. The concept of “micro‐hybrid” refers to offspring, including autodiploid and autotetraploid lineages, as well as those resulting from artificial gynogenesis, whose genome almost originates solely from the maternal parent but in which certain DNA fragments derived from the paternal parent insert. Distant hybridization and gynogenesis are vital techniques in fish genetics, breeding, and evolution. We highlight the prospective paths for research and application of distant hybridization and gynogenesis in fishes.

Spatial and temporal heterogeneity of soil salinity and ionic coupling relationship under the water-saving renovation of a typical irrigation district in arid and semi-arid areas - Shuya Yang; Qingfeng Miao; Haibin Shi; Yi Zhao; Xiaoyu Liu; Xin Nie; Weiying Feng; José Manuel Gonçalves; Tao Zhang; Yuxin Li; Yuli Luo (Science of The Total Environment, 2024)

Mechanism of Self-Assembled Celastrol-Erianin Nanomedicine for treatment of breast cancer - Jiahang Tian; Kun Chen; Qian Zhang; Chong Qiu; Haibo Tong; Jingnan Huang; Mingjing Hao; Junhui Chen; Wentong Zhao; Yin-Kwan Wong; Lei Gao; Piao Luo; et al. (Chemical Engineering Journal, 2024)

A preliminary result for centralized autonomous orbit determination of gnss constellation and lunar satellite based on inter-satellite link measurements - Peng Luo; Ye-Zhi Song; Jianhua Yang; Xiaogong Hu; Chengpan Tang; Kai Li; Qingfeng Wu (GPS Solutions, 2024)

Polycentric spatial Structure, digital economy and urban green sustainable development - Yiling Ding; Qingfeng Luo (Journal of Cleaner Production, 2024)

Exploring artificial intelligence and urban pollution emissions: "Speed bump" or "accelerator" for sustainable development? - Qingfeng Luo; Pengcheng Feng (Journal of Cleaner Production, 2024)

Vertically designed high-performance and flexible thermoelectric generator based on optimized PEDOT:PSS/SWCNTs composite films - Binjie Xia; Xiao-Lei Shi; Li Zhang; Jia Luo; Wen-Yi Chen; Boxuan Hu; Tianyi Cao; Ting Wu; Wei-Di Liu; Yanling Yang; Qingfeng Liu; Zhi-Gang Chen (Chemical Engineering Journal, 2024)

nZnO-based graphene/graphene oxide compounds inhibit methane metabolic pathways and lower the development of antibiotic resistance genes and virulence factors - Haibo Zhang; Lizhi Li; Qingfeng Xing; Jia Chen; Yihao Fan; Luo Dan; Yuhong Zhong; Yang Wang; Dongsheng Guo; Weikun Guan; Cheng Zhang (Journal of Cleaner Production, 2023)

Distribution and transformation of potentially toxic elements in crack under coal mining disturbance - Junchi Li; Qinxue Yu; Ruoxi Qian; Xin Xiao; Yan Liang; Ping Luo; Hui Wang; Yin Lu; Lili Xu; Qingfeng Liu; Yu Xiao (Environmental Monitoring and Assessment, 2023)

Temperature changes during the last deglaciation and early Holocene in southwest China - Weiwei Sun; Enlou Zhang; Qingfeng Jiang; Dongliang Ning; Wenlei Luo (Global and Planetary Change, 2023)

Enhancing maize yield through understanding the novel shoot-root interaction in morphology among hybrids with dense planting - Yupeng Zhu; Su Wang; Yunhao Li; Dan Wei; Ning Luo; Pu Wang; Qingfeng Meng (Field Crops Research, 2023)

Diverse water management in a preceding wheat crop does not affect maize yield but increases inter-annual variability: A six-year field study - Dan Wei; Ning Luo; Yupeng Zhu; Pu Wang; Qingfeng Meng (Field Crops Research, 2023)

Boosting hydrogen evolution on MoS2 via synergistic regulation of interlayer dislocations and interlayer spacing - Longlu Wang; Feiran Zhang; Ning Sun; Lingbin Xie; Ting Zhi; Qingfeng Zhang; Zhongzhong Luo; Xia Liu; Shujuan Liu; Qiang Zhao (Chemical Engineering Journal, 2023)

Predicting mobile users' next location using the semantically enriched geo-embedding model and the multilayer attention mechanism - Yao Yao; Zijin Guo; Chen Dou; Minghui Jia; Ye Hong; Qingfeng Guan; Peng Luo (Computers, Environment and Urban Systems, 2023)

Water replenishment to maize under heat stress improves canopy temperature and grain filling traits during the reproductive stage - Xinglong Wang; Ning Luo; Yupeng Zhu; Ye Yan; Haijiang Wang; Hejing Xie; Pu Wang; Qingfeng Meng (Agricultural and Forest Meteorology, 2023)

Analysis of groundwater flow through low-latitude alpine permafrost by model simulation: a case study in the headwater area of Yellow River on the Qinghai-Tibet Plateau, China - Shuhui Gao; Huijun Jin; Qingbai Wu; Victor F. Bense; Dongliang Luo; Qingfeng Wang; Yuzhong Yang; Wenwen Chang (Hydrogeology Journal, 2023)

Identification of DNA methylation and genetic alteration simultaneously from a single blood biopsy - Xiaomin Chen; Jiahui Liu; Jun Li; Yinpeng Xie; Zichen Yu; Lu Shen; Qingfeng Liu; Wei Wu; Qiang Zhao; Haoxiang Lin; Gaotong Liu; Qiuping Luo; et al. (Genes & Genomics, 2023)

Alleviating groundwater depletion while realizing food security for sustainable development - Dan Wei; Xinglong Wang; Ning Luo; Yupeng Zhu; Pu Wang; Qingfeng Meng (Journal of Cleaner Production, 2023)

Flame propagation characteristics of methane explosion under different venting conditions - Qiuhong Wang; Songling Jin; Zhenmin Luo; Aiping Dai; Qingfeng Wang; Zhouhao Li (Fuel, 2023)

An improved hybrid bream derived from a hybrid lineage of Megalobrama amblycephala (♀)×Culter alburnus (♂) - Dingbin Gong; Min Tao; Lihui Xu; Fangzhou Hu; Zehong Wei; Shi Wang; Yude Wang; Qingfeng Liu; Chang Wu; Kaikun Luo; Chenchen Tang; Rong Zhou; et al. (Science China Life Sciences, 2022)

Comparative genomic analysis of Mycoplasma anatis strains - Qi Zhou; Kaijie Mai; Dehong Yang; Junfa Liu; Zhuanqiang Yan; Cuifen Luo; Yangtong Tan; Sheng Cao; Qingfeng Zhou; Li Chen; Feng Chen (Genes & Genomics, 2021)

Serological characteristics of COVID-19 patients - Mi Zhou; Jing Zhong; Lei Bi; Pengcheng Shang; Yan Xing; Bo Wang; Jianlan He; Ying Xu; Tao Luo; Maohua Ma; Qingfeng Li (Infectious Diseases, 2020)

Mapping thermokarst lakes and ponds across permafrost landscapes in the Headwater Area of Yellow River on northeastern Qinghai-Tibet Plateau - Raul-David Șerban; Huijun Jin; Mihaela Șerban; Dongliang Luo; Qingfeng Wang; Xiaoying Jin; Qiang Ma (International Journal of Remote Sensing, 2020)

L-3-n-Butylphthalide reduces ischemic stroke injury and increases M2 microglial polarization - Fangfang Li; Qingfeng Ma; Haiping Zhao; Rongliang Wang; Zhen Tao; Zhibin Fan; Sijia Zhang; Guangwen Li; Yumin Luo (Metabolic Brain Disease, 2018)

Spectroscopic, Viscositic and Molecular Modeling Studies on the Interaction of 3′-Azido-Daunorubicin Thiosemicarbazone with DNA - Fengling Cui; Qingfeng Liu; Hongxia Luo; Guisheng Zhang (Journal of Fluorescence, 2014)

Serum complement C3 has a stronger association with insulin resistance than high sensitive C-reactive protein in non-diabetic Chinese - Bangqiong Wang; Qifu Li; Yuanjuan Jiang; Zhoujun Liu; Li Zhong; Rong Luo; Qingfeng Cheng; Hua Qing (Inflammation Research, 2011)

Matrix porosity calculation in volcanic and dolomite reservoirs and its application - Ning Li; Hongliang Wu; Qingfu Feng; Kewen Wang; Yujiang Shi; Qingfeng Li; Xinping Luo (Applied Geophysics, 2009)